The Impact of Financial Knowledge on College Students' Financial Behavior: A Systematic Literature Review - Azizah, Afifatun Nur; Susilaningsih, Susilaningsih; Noviani, Leny (Asian Journal of Management Analytics, 2024)
This research explores the influence of financial knowledge on the financial behavior of students. The low level of financial knowledge among students can lead to financial problems, such as high debt. The aim of this research is to provide a clearer framework regarding how financial knowledge influences the financial behavior of students. Using the PRISMA-based Systematic Literature Review (SLR) method, it shows that the higher the financial knowledge of students, the better their financial behavior, enabling them to manage their finances well, such as budgeting, managing debt, and saving. Financial education in higher education is crucial for shaping responsible financial behavior, so appropriate interventions can help students develop better financial skills for their future.